Detection and Genetic Diversity of a Novel Water Buffalo Astrovirus Species Found in the Guangxi Province of China - Fang, Qingli; Li, Mingyang; Liu, Haifeng; Chen, Kuirong; Du, Yanjie; Wen, Chongli; Wei, Yingyi; Ouyang, Kang; Wei, Zuzhang; Chen, Ying; Huang, Weijian (Frontiers in Veterinary Science, 2021)
Astroviruses (AstVs) are major causative agents of gastroenteritis and have been detected worldwide. Little is known about the prevalence of neurotropic AstVs in Chinese water buffaloes but a novel species which is associated with encephalitis and meningitis has recently been found. In this study, based on nested RT-PCR, rapid amplification of the 3'-cDNA end (3'-RACE) and next-generation sequencing (NGS), we examined the infection of AstVs in water buffaloes in the Guangxi province of China. The results showed that the AstV infection was found in 40% (6/15) of the farms examined, and the prevalence of AstV in their feces was 11% (33/297). In addition, two near-full-length and two complete open reading frame 2 (ORF2) genes of AstVs from fecal sources were sequenced. Phylogenetic analysis of the ORF2 sequences indicated three lineages of BufAstVs, BufAstV lineage 1 was close related to the BoAstV, lineage 2 was related to the BufAstVs and lineage 3 was classified as novel AstVs, which had a close relationship with the neurotropic/neurovirulent AstVs strains found in bovine, ovine and musks. Moreover, genomic a recombination between the BufAstV and BoAstV strains was identified. This is a novel study reporting the genetic diversity of BufAstV infection in China especially found the similar neurotropic strains from fecal sources of water buffaloes and it also provides details of the epidemiology, genetic recombination and interspecies transmission of BoAstV and BufAstV in water buffaloes from the Guangxi province of China.